PENGARUH BAHAN AJAR DWIBAHASA TERHADAP KETERAMPILAN KOMUNIKASI SISWA DI SANGGAR BIMBINGAN KAMPUNG BHARU MALAYSIA - Raditya Prasetia; Suci Perwita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education plays an essential role in preparing students to become high-quality human resources in the future. Mastery of more than one language, particularly Indonesian and Malay, is an important factor in supporting cross-cultural communication skills within the learning environment. This study aims to analyze the influence of bilingual teaching materials on students’ communication skills at Sanggar Bimbingan Kampung Bharu, Malaysia. The research employed a descriptive quantitative method, with data collected through observation, tests, and documentation involving 10 third-grade students. Data were analyzed using the Paired Sample T-Test to determine the significant difference between pretest and posttest scores. The results revealed a significance value of 0.000 (<0.05) with an average increase from 37.63% to 63.81%, indicating a positive effect of bilingual teaching materials on students’ communication abilities. These findings suggest that the use of two languages in teaching materials not only enhances students’ comprehension and confidence in communication but also helps create an inclusive and adaptive learning environment that supports the development of cross-cultural communication skills.